Use of vinasse as an additive in silages of Tithonia diversifolia (Hemsl) L. vc. IcaCuba Occ-10, alone and in mixture with Cenchrus purpureus cv. CT-608 - Rodríguez Hernández, R.; Fortes González, Dayleni; Rodríguez González, Yaisel; Domínguez Lima, Melanis; Casanova Rivera, Dainelis (Cuban Journal of Agricultural Science, 2025)
To evaluate the quality of silages of Tithonia diversifolia vc. IcaCuba Occ-10, alone or mixed with forage of Cenchrus purpureus cv. CT-608, preserved with or without vinasse, a completely random design was used, with a factorial arrangement (2x2) and 10 microsilos per treatment. All treatments showed similar dry matter content (P>0.05), lower than the recommended values (30-35 %). The inclusion of vinasse reduced the pH compared to the treatment without it (P<0.01). similarly, the dry matter:pH ratio improved when vinasse was included as an additive. The treatments of Tithonia alone showed a dark green color, the mixture of Tithonia and Cenchrus forages resulted in olive green with dark tones that disappeared when vinasse was added. It was the latter that had a coloration most in line with an excellent quality silage. In the silages with vinasse, a pleasant smell was obtained, similar to that suggested for silages of very good characteristics. The silages obtained from T. diversifolia, alone or mixed with C. purpureus cv. CT-608 forage, showed sufficient quality indicators to recommend their evaluation on a larger scale, even starting from materials with low dry matter contents. The organoleptic and chemical evaluation supports its stability and acceptability. The inclusion of vinasse in the preservation process of these silages is confirmed as an economical and effective strategy for the conservation of tropical forages, even forages with high protein content and high buffering capacity such as tithonia. Its use as an additive reduces the acid detergent fiber content, pH, and improves dry matter yield, the dry matter:pH ratio, and its organoleptic characteristics, such as color and odor.